Development of a prodrug of hydantoin based TACE inhibitor. Issue 16 (15th August 2017) - Tong, Ling; Kim, Seong Heon; Chen, Lei; Kosinski, Aneta; Shankar, Bandarpalle B.; Girijavallabhan, Vinay; Yang, De-Yi; Yu, Wensheng; Zhou, Guowei; Shih, Neng-Yang; Chen, Shiying; Hu, Mengwei; et al.
Graphical abstract: Abstract: Our research on hydantoin based TNF-α converting enzyme (TACE) inhibitors led to fused bi-heteroaryl hydantoin series that demonstrate sub-nanomolar potency (Ki) as well as excellent activity in human whole blood ( h WBA). However, lead compound2 posed some formulation challenges which prevented it for further development. A prodrug approach was investigated to address this issue. The pivalate prodrug3 can be formulated as stable neutral form and demonstrated improved DMPK properties when compared with parent compound.